2015
DOI: 10.1002/jbmr.2564
|View full text |Cite
|
Sign up to set email alerts
|

Does Diet-Induced Weight Loss Lead to Bone Loss in Overweight or Obese Adults? A Systematic Review and Meta-Analysis of Clinical Trials

Abstract: Diet-induced weight loss has been suggested to be harmful to bone health. We conducted a systematic review and meta-analysis (using a random-effects model) to quantify the effect of diet-induced weight loss on bone. We included 41 publications involving overweight or obese but otherwise healthy adults who followed a dietary weight-loss intervention. The primary outcomes examined were changes from baseline in total hip, lumbar spine, and total body bone mineral density (BMD), as assessed by dual-energy X-ray ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
100
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 99 publications
(293 reference statements)
12
100
1
1
Order By: Relevance
“…These reductions in total hip BMD were between 0.010 and 0.015 g/cm 2 , which corresponds to an approximate change of 1%-1.5% from pretreatment values [34]. While statistically significant, these diet-induced reductions in hip BMD are considerably less than those associated with bariatric surgery (RYGB specifically), which showed a decline of 8%-11% from presurgical values in the first 12 months post surgery [10,50,56,59,60].…”
Section: Effects Of Dietary Restriction On Bonementioning
confidence: 85%
See 3 more Smart Citations
“…These reductions in total hip BMD were between 0.010 and 0.015 g/cm 2 , which corresponds to an approximate change of 1%-1.5% from pretreatment values [34]. While statistically significant, these diet-induced reductions in hip BMD are considerably less than those associated with bariatric surgery (RYGB specifically), which showed a decline of 8%-11% from presurgical values in the first 12 months post surgery [10,50,56,59,60].…”
Section: Effects Of Dietary Restriction On Bonementioning
confidence: 85%
“…Similarly to bariatric surgery studies, a recent metaanalysis found a significant reduction in hip BMD after diet-induced weight loss interventions of 6-24 (but not 3) months in duration [34]. These reductions in total hip BMD were between 0.010 and 0.015 g/cm 2 , which corresponds to an approximate change of 1%-1.5% from pretreatment values [34].…”
Section: Effects Of Dietary Restriction On Bonementioning
confidence: 93%
See 2 more Smart Citations
“…1,2) Among these obesity-related complications, renal disease has been reported to be a significant issue. 3) High-fat diet induces renal lipid metabolism disorder, renal lipotoxicity and subsequent renal injuries.…”
mentioning
confidence: 99%